(untitled) (Research, Society and Development, 2021)
This paper aims to analyze Brazilian Law No. 12,305 of August 02, 2010 entitled National Solid Waste Policy, specifically in the obstacles to the completion of the regulation of the reverse logistics process and the main objectives, principles, and instruments of this policy in line with the pillars of sustainability. Analyses were performed through bibliographical research enabling the contextualization of the theme. It is perceived that the Law is very well elaborated, favoring sustainable regional development; however, the lack of public management and health issues such as the new coronavirus pandemic make it difficult to complete its implementation.